Analisis Faktor Yang Mempengaruhi Perilaku Nasabah Perbankan Konvensional Beralih Ke Perbankan Syariah (Studi Empiris Pada Mahasiswa Perguruan Tinggi di D.I.Y) - Ilham Maulana Saud; Iman Teguh; Peni Nugraheni (Universitas Trunojoyo Madura, 2018)
This study aims to analyze and prove empirically the influence of knowledge, religiosity, accessibility, and extra curricular islamic program to conventional banking customer behavior that switch to sharia banking. The subjects of this study are students of accounting study programs that become conventional banking customers and switch to sharia banking, whether really switching or not really switching. The object of this study is the institutions of college in the Special Region of Yogyakarta. In this study the sample of 82 respondents selected using purposive sampling method. The analysis used in this research is multiple linear regression analysis using SPSS 24.0. Based on the analysis that has been done obtained the result that the knowledge and extra curricularislamic program does not affect the behavior of conventional banking customers to switch to sharia banking. While religiosity and accessibility proved to have a positive and significant effect.